2010
DOI: 10.1111/j.1464-410x.2010.09599.x
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal magnetic resonance imaging has limited clinical ability to preoperatively predict pT3 prostate cancer

Abstract: to the 982 patients without imaging. Of the 110 patients with histopathologically organ-confined disease, 81 (74%) were correctly diagnosed as such on erMRI, whereas 29 (26%) were felt to have cT3 disease and constituted false-positives. Among the 69 patients with pT3 disease, erMRI correctly predicted 30 (43%), whereas 39 (57%) were incorrectly considered organ-confined.• The overall sensitivity and specificity for diagnosing pT3 disease was 43% and 73%.• When stratified by pT3a and pT3b, the sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
3
25
1
1
Order By: Relevance
“…The clinical benefit of preoperative MRI of the prostate is discussed controversially. Although MRI is widely accepted as the most reliable method for the local staging of PCa [1], some authors argue that it has little influence on therapeutic decision making [17]. In our study, both readers reached good sensitivities (80 % and 90 %) and fair specificities (74 % and 82 %) for ECE detection per patient.…”
Section: Urogenital Tract 799mentioning
confidence: 45%
“…The clinical benefit of preoperative MRI of the prostate is discussed controversially. Although MRI is widely accepted as the most reliable method for the local staging of PCa [1], some authors argue that it has little influence on therapeutic decision making [17]. In our study, both readers reached good sensitivities (80 % and 90 %) and fair specificities (74 % and 82 %) for ECE detection per patient.…”
Section: Urogenital Tract 799mentioning
confidence: 45%
“…[11,25,30] Our results showed that mp-MRI had 95% specificity, 80% positive predictive value for ECE, and 91% specificity regarding primary tumor localization. A previous study reported that the positive predictive value of mp-MRI for ECE was highest in the intermediate-and high-risk groups of patients.…”
Section: Discussionmentioning
confidence: 58%
“…32 However, each technique has one or more limitations, such as no standard parameters or low accuracy in central region of the gland. 33 Particularly for endorectal coil MRI, while it had been reported to have advanced sensitivity and specificity for detecting T3 disease over 90%, controversy still exists over the role of endorectal coil MRI of the prostate in detecting locally advanced disease, 34,35 with unique complications including rectal bleeding, erosion and proctitis. Considering these limitations and cost effectiveness, these functional images and endorectal coil MRI were not routinely conducted in our institution.…”
Section: Discussionmentioning
confidence: 99%